Enhancing Students' Critical Thinking Skills in Madrasah Ibtidaiyah through Problem-Solving Learning - Juhji, Juhji; Rismawati , Nita; Nuangchalerm, Prasart (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2024)
This study analyzes the impact of problem-solving learning on the critical thinking skills students. A quasi-experimental method with a pretest-posttest control group design was used. The sample consisted of 5th-grade students from Madrasah Ibtidaiyah Negeri 2 Serang, with 27 in the experimental class and 27 in the control class. Data collection involved observation and tests using a validated multiple-choice instrument. Normality and homogeneity tests preceded data analysis using the t-test. Results showed significant improvements in both classes, with the experimental class implementing the problem-solving model outperforming the control class using conventional methods. The t-test significance (2-tailed) was 0.007, indicating a significant difference in critical thinking skills between the groups. This finding supports the effectiveness of active learning approaches in fostering higher-order thinking skills where developing critical thinking is essential to fulfilling human responsibilities in living a meaningful life.